Effects of a Smartphone Application on Knowledge Discharge Outcome among Patients with Mild Traumatic Brain Injury - ทวีคูณ, ราชวัช; แพรขาว, ชัจคเณค์ (Journal of The Royal Thai Army Nurses, 2019)
The purpose of this quasi-experimental research was to study the Effects of a smartphone application on knowledge discharge outcome among patients with mild traumatic brain injury. The sample group were 66 mild traumatic brain injury patients arrived at the Emergency Department. They were aged at least 18 years. The Glasgow Coma Scale equals to 15 points. The participants were purposive sampling into the controlled and experimental group, 33 for each group. The experimental group was received the suggestion for observed neurological system symptoms via the smartphone application. The controlled group was received the suggestion I accordance with the nursing standards. The data were collected by using the interview on the mild traumatic brain injury patients. All of the instruments were validated for content validity 0.98 by 5 professionals. When analyzed and compared the difference of knowledge scores within the group and between the controlled and experimental group, the Paired t-test and Independent t-test are used. The research results reveal that the experimental group has higher knowledge scores after the trial than before the trial with statistical significance 0.05 (t = 15.38, p < 0.001). The knowledge scores of the experimental group are higher than the controlled group with statistical significance at level of 0.05 (t = 3.88, p < 0.001).